A Versatile Synthetic Affinity Probe Reveals Inhibitory Synapse Ultrastructure and Brain Connectivity** - Khayenko, Vladimir; Schulte, Clemens; Reis, Sara L.; Avraham, Orly; Schietroma, Cataldo; Worschech, Rafael; Nordblom, Noah F.; Kachler, Sonja; Villmann, Carmen; Heinze, Katrin G.; Schlosser, Andreas; Schueler-Furman, Ora; et al. (Angewandte Chemie International Edition, 2022)
Visualization of inhibitory synapses requires protocol tailoring for different sample types and imaging techniques, and usually relies on genetic manipulation or the use of antibodies that underperform in tissue immunofluorescence. Starting from an endogenous ligand of gephyrin, a universal marker of the inhibitory synapse, we developed a short peptidic binder and dimerized it, significantly increasing affinity and selectivity. We further tailored fluorophores to the binder, yielding “Sylite”—a probe with outstanding signal-to-background ratio that outperforms antibodies in tissue staining with rapid and efficient penetration, mitigation of staining artifacts, and simplified handling. In super-resolution microscopy Sylite precisely localizes the inhibitory synapse and enables nanoscale measurements. Sylite profiles inhibitory inputs and synapse sizes of excitatory and inhibitory neurons in the midbrain and combined with complimentary tracing techniques reveals the synaptic connectivity.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Dimerization; Fluorescent Probes; Neuroscience; Peptides; Super-Resolution Microscopy